Fumigant and Repellent Effects of Essential Oil Fractions of Mentha piperita against Tribolium castaneum (Coleoptera: Tenebrionidae) - Syam, Sunaryo; Harahap, Idham Sakti; Dadang, NFN (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Tribolium castaneum is one of the important stored-product pests in tropical countries. Fumigation with phosphine is the most commonly method to control T. castaneum. However, long-term application of phosphine will cause resistance. The aims of this research were to study the effects of fumigant and repellent of peppermint oil Mentha piperita fraction against T. castaneum, and to identify the compounds contained in the active fraction. This research was conducted in Entomology Laboratory Seameo Biotrop and Forensic Laboratory of Indonesian Police Headquarters Jakarta, from January to October 2016. Peppermint oil was extracted by distillation from the leaves of M. piperita. Peppermint oil was fractionated by counter-current distribution method using three solvents: n-hexane, ethyl acetate, and methanol. Then, the three fractions were tested as fumigant and repellent against T. castaneum. The active fraction of essential oils were identified by GC-MS. The n-hexane fraction of peppermint (HFP) was the active fraction caused mortality on larvae and adults of Â T. castaneum at 72 hours after fumigation. The LC95 values for the adults andÂ  larvae was 1.9 % and 9.43 % , respectively. Sublethal concentration of HFP showed inhibitory activity on larvae development. Percentage of pupae transformed from treated larvae was 48.67-74.91 % and percentage of adults emerged was 9.12-16.59 %. The repellent activity of HFP on adults of T. castaneum was 86.7 % at 72 hours after treatment. The dominant compounds of HFP was Î²-pinene, limonene, isopulegol, menthone, isomenthon, menthol, pulegone, and trans-carane. The HFP or its compounds was potential to be develoved as botanical insecticides.